2004
DOI: 10.1016/j.ijhydene.2003.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Biological production of hydrogen from glucose by natural anaerobic microflora

Abstract: Palm oil mill e uent (POME) sludge, sludge compost from Malaysia and CREST compost from Philippines were collected for the study. The capability of these micro ora to produce hydrogen was examined with 500 ml artiÿcial wastewater containing 1% glucose, 0.2% yeast extract and 0.018% magnesium chloride hexahydrate under anaerobic fermentation in a batch culture. The micro ora in POME sludge, sludge compost and CREST compost were found to produce signiÿcant amounts of hydrogen. The maximum production yield of hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
3
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(70 citation statements)
references
References 21 publications
(28 reference statements)
4
57
3
6
Order By: Relevance
“…The results of present study agreed with Morimoto et al [7] they reported by increasing the yeast extract from 0.2-0.4%, the hydrogen yield of 2.1 mol −1 mole of glucose was increased by 30%, but with further increase to 0.8%, the hydrogen yield was decreased by 50%. They reasoned that to the nitrogen concentration in fermentation medium, since they used POME as substrate with mixed culture under thermophilic condition.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The results of present study agreed with Morimoto et al [7] they reported by increasing the yeast extract from 0.2-0.4%, the hydrogen yield of 2.1 mol −1 mole of glucose was increased by 30%, but with further increase to 0.8%, the hydrogen yield was decreased by 50%. They reasoned that to the nitrogen concentration in fermentation medium, since they used POME as substrate with mixed culture under thermophilic condition.…”
Section: Resultssupporting
confidence: 93%
“…[11] they found the yeast extract using 0.1% was the best nitrogen source for hydrogen production and finally with Morimoto et al [7] they reported that by using 0.2% of yeast extract, the hydrogen yield was the best among the nitrogen source they used. Lower final culture pHs for yeast extract as shown in Table 2 and 4 indicated that more acids was produced suggested that the substrate utilization was better for hydrogen production than other nitrogen sources.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Estudios plantean la producción de biohidrógeno a partir de compuestos biológicos y microorganismos, con el empleo de cepas de Thermoanaerobacterium thermosaccharolyticum (O-Thong et al, 2008) y Clostridium pasteurianum (Lin y Lay, 2004). Estas cepas pueden ser obtenidas en medios con efluentes líquidos como sustrato (Morimoto et al, 2004;Atif et al, 2005). Estos procesos biológicos abren nuevas vías en la producción de bioenergía (Morimoto et al, 2004), disminuyendo la dependencia a los combustibles fósiles, los costos de capital y las emisiones de contaminantes como el CO 2 , debido a que el hidrógeno posee un calor específico de 142 MJ/ kg, superior al del metano (56 MJ/kg) y al de la gasolina (47 MJ/kg) (Lam y Lee, 2011), y su proceso genera como producto agua pura (Atif et al, 2005;Wu et al, 2009).…”
Section: Aguas Residualesunclassified
“…Glucose and xylose are produced at a concentration ratio of 55-65% to 35-45% during the saccharidification of some organic wastes like wood, paper, agricultural by-products or crops (Ahring et al 1996, Lavarack et al 2002. Fermentative hydrogen production from glucose using mixed microflora has been well studied (Fang and Liu 2002, Lin and Chang 1999, Zheng and Yu 2004, Morimoto et al 2004). However, fermentative hydrogen production from xylose using mixed microflora has not been well reported.…”
Section: Introductionmentioning
confidence: 99%